2011
DOI: 10.4028/www.scientific.net/amm.94-96.316
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Combined Connection with Bolts and Welds

Abstract: The combined connection with welds and bolds has advantages of both welds and bolts connections, and can be widely used in reinforcing the joint in steel structure. In this paper, the Finite Element Method (FEM) was taken to analyze the carrying capacity of the combined connection with bolts and welds, and the results ware compared with those come from experimental investigation. Further analysis based on FEM ware performed to research the failure mode and bearing performance of the combined connection and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some Chinese scholars [12][13][14] have studied the working behaviour of the joints combined high-strength bolts and welds with finite element method. The availability of FEM in bolts and welded joints is verified through these study because the bearing capacity and deformation characteristic of the FEM results have a higher consistency with the tests results.…”
Section: Introductionmentioning
confidence: 99%
“…Some Chinese scholars [12][13][14] have studied the working behaviour of the joints combined high-strength bolts and welds with finite element method. The availability of FEM in bolts and welded joints is verified through these study because the bearing capacity and deformation characteristic of the FEM results have a higher consistency with the tests results.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, authors [3][4][5] found that the bearing capacity of the combined connection with bolts and welds was not equal to simple summation of weld and bolt bearing capacities and differ from the bearing capacity design value given in the specification. In addition, Dongxu et al [6] found that the weld-to-bolt strength ratio had more influence on the bearing capacity of joint in the design of connection.…”
mentioning
confidence: 99%